'It Is Not the Beliefs but the Crime That Matters': Post-War Civil Liberties Debates in Canada and Australia - Clément, Dominique (Labour History, 2004)
In both Canada and Australia, a modern rights movement dedicated to the preservation of individual rights irrespective of creed, class, beliefs, race or ethnicity emerged in the 1930s. One of the central themes in the early years of both movements was the treatment of communists and organised labour amid concerns over state abuse of freedoms of speech, association and due process. The Australian Council for Civil Liberties and the Canadian Civil Liberties Union were founded in the 1930s to counter increasing tendencies of the state to suppress political rights, most often directed against the radical left. However, divisions within the political left, most notably between social democrats and communists, as well as weaknesses in the legal system created significant obstacles to the civil liberties movement in both countries. The following article explores the key themes in the early Australian and Canadian civil liberties movement by comparing two separate national social movements operating within a similar legal, political and social context. Debates over the Communist Party Dissolution Bill (1950) and subsequent referendum (1951) in Australia and the espionage commission (1946) in Canada represented high profile post-war debates on civil liberties issues in both countries, arising out of attempts by the federal government to suppress communism.